Carbon Materials Derived from Poly(aniline-co-p-phenylenediamine) Cryogels - Milakin, Konstantin A. (Polymers (Basel), 2019)
Nitrogen-containing carbon derivatives were prepared by the carbonization of poly(aniline-co-p-phenylenediamine) cryogels in inert atmosphere. Lower aniline fraction in the comonomer mixture used for preparation of the cryogels led to the decrease of their thermal stability, a consequent increase of carbonization degree, and less defective structure of carbonized materials. The resulting carbonaceous products had up to 4 orders of magnitude higher specific surface area than their respective cryogel precursors, the highest value 931 m(2) g(−1) being achieved for carbonized poly(p-phenylenediamine) cryogel. Electrochemical characterization of the carbon derivatives demonstrated that the decrease in aniline concentration during the synthesis of the precursor cryogels led to higher gravimetric capacitance for corresponding carbonized materials. These materials can potentially be used for energy storage applications.